2020
DOI: 10.3390/su12124982
|View full text |Cite
|
Sign up to set email alerts
|

Urban Green Space Distribution Related to Land Values in Fast-Growing Megacities, Mumbai and Jakarta–Unexploited Opportunities to Increase Access to Greenery for the Poor

Abstract: Many studies on disparities in the distribution of urban green space (UGS) focus on the quantity and accessibility of designated open spaces. However, when all types of UGS, including unmanaged green areas, are accounted for, claims of green space distributive injustice become more complicated. We conducted a preliminary investigation questioning the common Global North assumption that the poor have less access to the benefits of green space, using the cities of Mumbai and Jakarta as case studies as, in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Several previous studies conducted in Asia indicated that factors such as the size, distance and shape of structures, their diversity and variation and their location in the green network all contribute to their perception and use, resulting in improved physical and cognitive performance, as well as improved well-being for city dwellers [11,24,34]. [63] found that the lower land value districts had more vegetation coverage with a higher vegetation density, mainly due to a large quantity of unmanaged greenery. It is worth noting that small green spaces may provide less extensive opportunities for recreation so contribute less health benefits than large-size green spaces [40].…”
Section: Discussionmentioning
confidence: 93%
“…Several previous studies conducted in Asia indicated that factors such as the size, distance and shape of structures, their diversity and variation and their location in the green network all contribute to their perception and use, resulting in improved physical and cognitive performance, as well as improved well-being for city dwellers [11,24,34]. [63] found that the lower land value districts had more vegetation coverage with a higher vegetation density, mainly due to a large quantity of unmanaged greenery. It is worth noting that small green spaces may provide less extensive opportunities for recreation so contribute less health benefits than large-size green spaces [40].…”
Section: Discussionmentioning
confidence: 93%
“…Studies which covered Indian cities such as Nagpur (S. Lahoti, A. Lahoti et al, 2019), Gandhinagar;Chandigarh;Delhi (Mitra, 2013); Bangalore; Jaipur (Chaudhry, Bagra et al, 2011), Mumbai (Sathyakumar, Ramsankaran et al, 2019. Hwang, Nasution et al (2020) suggest that Indian cities lack the amount of Greenspace per capita as per WHO guidelines. Even when we divide the city into different zones, most of the zones do not fit the greenspace requirements as per any guidelines.…”
Section: Greenspaces and Green Spacesmentioning
confidence: 99%
“…Landuse change from green open space can be analyzed using the GIS method to see the level of green open spaces availability in urban areas. The distribution of green open space is also adjusted to the quantity and accessibility (Hwang et al 2020). Quantity can be interpreted as the green open space must be balanced and can support urban functions.…”
Section: A Flood In Indonesiamentioning
confidence: 99%